2007
DOI: 10.1111/j.1365-2362.2007.01772.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular stiffness in familial hypercholesterolaemia is associated with C‐reactive protein and cholesterol burden

Abstract: Both high cholesterol burden and vascular inflammation are not only associated with atherosclerosis, but also contribute to the development of arterial stiffness in FH patients. Early detection of hypercholesterolaemia in FH patients is warranted to prevent the untoward pathophysiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
35
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
6
35
1
2
Order By: Relevance
“…In our study, as shown in Fig. 1a, the cholesterol-year score was positively correlated with the carotid IMT ( r  = 0.389, p  < 0.05), which is consistent with the findings in a previous study [11]. In addition, the serum sulfatide levels were also positively correlated with the carotid IMT ( r  = 0.838, p  < 0.001) (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In our study, as shown in Fig. 1a, the cholesterol-year score was positively correlated with the carotid IMT ( r  = 0.389, p  < 0.05), which is consistent with the findings in a previous study [11]. In addition, the serum sulfatide levels were also positively correlated with the carotid IMT ( r  = 0.838, p  < 0.001) (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Here, in HeFH subjects, we showed an independent association between TCB and calcified coronary atherosclerotic burden that expands previous results on arterial stiffening and thickening (23). In young patients under 45 years we report the high prevalence of CAC presence in correlation with the cholesterol burden at diagnosis suggesting a potential role of early exposure to elevated cholesterol levels.…”
supporting
confidence: 88%
“…Recent meta-analysis data have indicated that the increased risk for CVD and related events are, in part, attributable to stiffening of the aorta as assessed by aortic pulse wave velocity (aPWV) (3). Importantly, nearly 50% of Americans have total cholesterol values above the desirable level (21), which, in turn, promotes aortic stiffening (13,23,42). Thus, gaining insights for the mechanisms by which traditional risk factors, such as hypercholesterolemia, promote aortic stiffening is of clinical importance.…”
mentioning
confidence: 99%